PRICE VOLATILITY SPILLOVER IN DOMESTIC COTTON MARKETS OF PAKISTAN: AN APPLICATION OF DCC-MGARCH MODEL* - S. Sehar; M. Ling; S. Hassan; J. Han (Journal of Animal and Plant Sciences, 2018)
The identification of interdependencies among various product markets is imperative both from the macro and microeconomic viewpoint. This paper examines price volatility spillover effects among ten domestic cotton markets (7 from Punjab and 3 from Sindh) of Pakistan by employing the DCC-MGARCH model. Analysis is done using quarterly st wholesale prices of seed cotton from 1 quarter of the year 1991 till second quarter of 2017. Results indicate that seed cotton prices are volatile in all the domestic markets considered as well as volatility is persistent. Dynamic conditional correlation coefficient shows that seed cotton markets have positive conditional correlation with each other. It is concluded from the study results that because of volatile nature of cotton prices, farmers profit is at risk. This further suggests the governmentsinvestment in road and infrastructure and intervention in seed cotton markets to keep the markets stable and support cotton farmers against risk. Jel Classification: C22 ,C32 ,Q11 ,Q13. et. al., 2013) . Marketing chain of seed cotton is
Keywords: Cotton; price volatility spillover; volatility clustering; volatility persistance; DCC-MGARCH